Proses Kreatif Penulisan Novel Berbahasa Jawa Kompetitif Karya Siti Aminah - Kumayah, Achifatul; Supriadi, Didik; Fuadhiyah, Ucik (Faculty of Languages and Arts, Universitas Negeri Padang, 2025)
This study examines Siti Aminah's creative process and writing strategies in producing competitive Javanese novels. The focus of the study includes the stages of the creative process and the strategies used to win novel writing competitions. This study uses an expressive approach, which focuses on the relationship between literary works and the inner world of the author, with descriptive qualitative methods. Research data was obtained through interviews with Siti Aminah and documentation of the novels Sengara Mati and Truntum. The results of the study reveal that the creative process undergone by Siti Aminah follows the four stages of Wallas, namely: the preparation stage, which involves collecting writing materials; the incubation stage, which involves deep reflection on previously written works; the illumination stage, which involves pouring ideas through mind mapping to organize the plot; and the verification stage, which involves self-evaluation for competition requirements and the involvement of professional editors for general publication. The findings also reveal that there are five strategies applied by Siti Aminah to produce high-quality works in the context of competitions, including: (1) selecting themes related to feminism and Yogyakarta culture, (2) using Javanese language that is easy to understand, (3) crafting an engaging narrative, (4) participating in literary competitions, and (5) effective post-competition publication and distribution strategies. This study concludes that the creative process in competitive novel writing depends not only on individual creativity, but also on the author's strategic ability to adapt to the demands of the competition.